PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KONTEKSTUAL CTL (CONSTEXTUAL TEACHING AND LEARNING) TERHADAP HASIL BELAJAR FISIKA SISWA MATERI POKOK LISTRIK DINAMIS DI KELAS X SMA NEGERI PADANGSIDIMPUAN - Sari Wahyuni Rozi Nasution (JURNAL PhysEdu (PHYSICS EDUCATION), 2023)
This research aimed to examine the effect of usin learning model constextual CTL(Constextual Teaching And Learning) to result of the subject Physical The Second Law OfDynamic electric at X Grade of SMA N 6 Padangsidimpuan, because the writer found the problem of low achievement physics subject matter Dynamic electric at the school.This research conducted at SMA Negeri 6 Padangsidimpuan. This research time for 3 months ie from April to June of 2013.This research done by using descriptive and experimental methods. The population in this research are all of students at X grade SMA N 6 Padangsidimpuan consisting of 8 classes totaling 328 students. The sampling technique used is random sampling technique obtained sample totaling 80 student. The technique of collecting data are observation and test. And data analysis technique that writer use are descriptive analysis and inferential statistical analysis, using the test”t”.Based on the calculation in the descriptive analysis of the effect of using learning model constextual CTL (Constextual Teaching And Learning) at X grade of SMA N 6Padangsidimpuan obtained average value 2,83, include to category “Good”, average value of the subject matter of student learning outcomes Dynamic electric before experiment was 47,50, these are in the category “Failed”. And the average value of the subject matter of student learning outcomes The Second Law Of Dynamic electric after experiment of 75,80, and this are include to category “Good/Through”.Based on calculation performed tcount values abtained at 23,91 with a sample of 80, with db = 80 – 1 = 79. ttable values at the 5% significance level of 99 is 5,981. Based on the calculation above, it can be concluded that the tcount is greater than ttable (tcount >ttable = 23,91> 5,981).Means that the hypothesis formulated in this study can be accepted or approved. It means that there is a significant influence between learning model constextual CTL(Constextual Teaching And Learning) to learning outcomes of the subject matter Physical The Second Law Of Dynamic electric X grade of SMA N 6 Padangsidimpuan.